A natureza do parto e o parto natural - Oliveira, Fernanda Mayra Mendonça de (2014)
This work has as its object the speeches about childbirth studied from the analysis of discourse. Using speeches about childbirth as relays for public policies and between technicians and users of the health system in Aracaju, social movements and the humanization of childbirth step to formulate the question: were the modes of naturalization in childbirth practices reflecting modeling conduct, production of stereotypies and determinism in the effects of this experience? The goal is to study how the disciplining and control bodies traverse the speeches on labor and the extent to which discourses about childbirth presented as progressive or liberating subdues can produce. To this end, the article shows a brief genealogy of the birth, the trajectory of their practices, biopolitical crossings and State policies, and discuss and give visibility to the affective, economic, aesthetic, ecological implications. The trajectory analysis ends up unfolding the relationship between the proposed humanized labor and the emergence of a pedagogy of childbirth and pregnancy anchored in the role of Doula. The research method is based on the concepts of institutional analysis implication and superimplication, regarded to research on the implications of the research are considered the essence of scientific work.